2011
DOI: 10.1007/s11999-011-1970-3
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Technique: A Minimally Invasive Approach to Scapula Neck and Body Fractures

Abstract: Background The approach of choice for open reduction internal fixation of displaced fractures involving the scapula neck or body is from posterior. We describe a new approach that minimizes the surgical insult to the soft tissues but preserves the ability to restore alignment and stability to the fracture. Description of Technique Based on the fracture pattern, incisions are made along the anatomic bony perimeter to access the scapula borders for reduction and fixation. Since the incisions are centered over si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
54
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(54 citation statements)
references
References 23 publications
(30 reference statements)
0
54
0
Order By: Relevance
“…These columns of bone are reliably accessible through the MJ approach. 20 Another recent study by the same group compared the exposure of the MJ approach with or without release of the posterior deltoid. 7 They found the surface area exposed to be 30.2 cm 2 with the deltoid detached compared to only 16.8 cm 2 in these specimens.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These columns of bone are reliably accessible through the MJ approach. 20 Another recent study by the same group compared the exposure of the MJ approach with or without release of the posterior deltoid. 7 They found the surface area exposed to be 30.2 cm 2 with the deltoid detached compared to only 16.8 cm 2 in these specimens.…”
Section: Discussionmentioning
confidence: 99%
“…19 Most recently, 1 group of authors even described a less extensile technique using 2 small incisions to access the important areas of the scapula. 20 Although most traditional approaches involve exposing the entire bone, it has become apparent that the bony landmarks critical for fixation are all located on the periphery.…”
Section: Introductionmentioning
confidence: 99%
“…A DASH score between 0 and 29 is considered to be the point where the patient no longer considers their upper limb disorder is a problem (20). Past studies reported mean DASH score between 8.1 and 14 for all patients who underwent surgical interventions for scapular neck and body fractures (10,13,16,18,19,21). The patient-reported functional outcome using SF-36 questionnaire scored between 70 and 89.6 (comparable to normal healthy population 61 to 84), with exception to two subcategories, i.e., REE (role limitations due to emotional problems) and REP (role limitations due to physical health).…”
Section: Discussionmentioning
confidence: 99%
“…[13] A modified Judet approach utilizes a similar incision to allow access to the internervous interval between the infraspinatus and teres minor without reflection of the infraspinatus, which minimizes soft tissue stripping and risk of injury to the neurovascular pedicle, while still providing adequate access to the thick bone of the lateral border of the scapula where the best bone stock for fixation is located. [14] A minimally invasive posterior approach has been described which uses multiple small incisions to gain access to the same internervous interval along the thick borders of the scapula, [15] but limited skin incisions may prove challenging for surgeons who rarely operate on the posterior shoulder or in obese patients in whom bony landmarks are obscured. The so-called "two-portal" approach utilizes the same internervous interval but also mobilizes the infraspinatus caudally to provide access to superior border of the scapula between the infraspinatus and supraspinatus, [16] with the added risk of injury to the suprascapular neurovascular bundle.…”
Section: Discussionmentioning
confidence: 99%